2021
DOI: 10.3389/fcvm.2021.749686
|View full text |Cite
|
Sign up to set email alerts
|

Management of High Cardiovascular Risk in Diabetic Patients: Focus on Low Density Lipoprotein Cholesterol and Appropriate Drug Use in General Practice

Abstract: This study aimed to evaluate the management of high cardiovascular risk (CVr) in the patients with diabetes by exploring the prescribing behavior in a setting of general practitioners (GPs). A retrospective cohort study was carried out using the data recorded between 2018 and 2020 in the clinical database of 10 GPs. Diabetes was defined using the International Classification of Diseases (ICD-9-CM) coding (250*) or using the laboratory parameters (hyperglycemia condition: ≥126 mg/dL). A cohort was described str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Cholesterol-lowering therapy is the mainstay in primary and secondary prevention of cardiovascular diseases ( 69 , 70 ). Statins effectively decrease serum LDL-C and sdLDL-C while increasing HDL-C levels and reduce the susceptibility of apo B of LDL to undergo oxidation and glycation.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Cholesterol-lowering therapy is the mainstay in primary and secondary prevention of cardiovascular diseases ( 69 , 70 ). Statins effectively decrease serum LDL-C and sdLDL-C while increasing HDL-C levels and reduce the susceptibility of apo B of LDL to undergo oxidation and glycation.…”
Section: Clinical Relevancementioning
confidence: 99%
“…The complexity of this clinical scenario makes generally very hard the appropriateness of the pharmacological treatment in the real world, as previously shown ( Squadrito et al, 2020 ; Rottura et al, 2021 ). An optimal management of diabetes, hypertension, and other cardiovascular risk factors in patients with CAD is essential, especially in the elderly.…”
Section: Discussionmentioning
confidence: 97%
“…Any variation within defined ranges is investigated and back-submitted to each participating GP, in order to receive immediate feedback about data quality and completeness. Data quality and completeness have been already validated in previous drug-utilization studies ( Barbieri et al, 2020 ; Squadrito et al, 2020 ; Rottura et al, 2021 ). The database contains the information recorded during 2018–2020 on each GP’s patient, aged at least 18 years old, including age, sex, height, weight and body mass index (BMI), systolic blood pressure (SBP) and diastolic blood pressure (DBP), information on lifestyle (alcohol, smoke), and data on diagnostic laboratory exams including fasting plasma glucose (FPG), glycated haemoglobin (HbA1c), and lipid profile.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, SGLT-2 inhibitors are one of the main classes of drugs recommended by the ADA guidelines as the first-line treatment for glycemic control in patients with CVD and CKD, in replacement of metformin which remains the main oral hypoglycemic agent recommended to patients with diabetes [ 31 ]. However, several studies have shown poor under-prescription of SGLT-2 in clinical practice [ 32 , 33 ]. Metformin prescriptions should be evaluated taking into account the renal function status of the patients.…”
Section: Discussionmentioning
confidence: 99%